Aldehyde dehydrogenase 2 protects against abdominal aortic aneurysm formation by reducing reactive oxygen species, vascular inflammation, and apoptosis of vascular smooth muscle cells - Tsai, Shih-Hung; Hsu, Lung-An; Tsai, Hsiao-Ya; Yeh, Yung-Hsin; Lu, Cheng-Yo; Chen, Po-Chuan; Wang, Jen-Chun; Chiu, Yi-Lin; Lin, Chih-Yuan; Hsu, Yu-Juei (The FASEB journal, 2020)
Mitochondrial aldehyde dehydrogenase 2 (ALDH2) is an enzyme that detoxifies aldehydes by converting them to carboxylic acids. ALDH2 deficiency is known to increase oxidative stress. Increased oxidative stress plays a pivotal role in abdominal aortic aneurysm (AAA) pathogenesis. Reactive oxygen species (ROS) promote degradation of the extracellular matrix (ECM) and vascular smooth muscle cell (VSMC) apoptosis. Reducing oxidative stress by an ALDH2 activator could have therapeutic potential for limiting AAA development. We hypothesized that ALDH2 deficiency could increase the risk for AAA by decreasing ROS elimination and that an ALDH2 activator could provide an alternative option for AAA treatment. The National Center for Biotechnology (NCBI) Gene Expression Omnibus (GEO) database was used. Human aortic smooth muscle cells (HASMCs) were used for the in vitro experiments. Gene-targeted ALDH2*2 KI knock-in mice on a C57BL/6J background and apolipoprotein E knockout (ApoE KO) mice were obtained. An animal model of AAA was constructed using osmotic minipumps to deliver 1000 ng/kg/min angiotensin II (AngII) for 28 days. Patients with AAA had significantly lower ALDH2 expression levels than normal subjects. ALDH2*2 KI mice were susceptible to AngII administration, exhibiting significantly increased AAA incidence rates and increased aortic diameters. Alda-1, an ALDH2 activator, reduced AngII-induced ROS production, NF-kB activation, and apoptosis in HASMCs. Alda-1 attenuated AngII-induced aneurysm formation and decreased aortic expansion in ApoE KO mice. We concluded that ALDH2 deficiency is associated with the development of AAAs in humans and a murine disease model. ALDH2 deficiency increases susceptibility to AngII-induced AAA formation by attenuating anti-ROS effects and increasing VSMC apoptosis and vascular inflammation. Alda-1 was shown to attenuate the progression of experimental AAA in a murine model.